Microwave-Mediated Suzuki–Miyaura Cross-Couplings of Thioether- and ortho-Substituted Methylphenylboronic Acid Esters - Baltus, Christine B.; Press, Neil J.; Spencer, John (Synlett, 2012)
Hiterto unsuccessful cross-couplings of ortho-substituted or thioether-substituted methylphenylboronates have now been achieved, under microwave conditions, enabling the synthesis of a library of novel biaryls. Tetrakis(triphenylphosphine)palladium and various bases, for example, sodium carbonate or cesium fluoride, were found to mediate the crucial C–C bond-forming cross-coupling reaction.
Keywords: palladium; catalysis; cross-coupling; biaryls; microwaves